The Effect of Incentives and Islamic Compensation on Agent Loyalty with Job Satisfaction as a Mediating Variable in Sharia Insurance in Medan City - Ade Nurul Kaidah Sinaga; Fauzi Arif Lubis; Wahyu Syarvina (Fakultas Syariah IAIN Langsa, 2026)
Ideally, incentive systems and Islamic compensation implemented in Sharia insurance companies are expected to directly enhance agent loyalty through fair and Sharia-compliant rewards. However, in reality, agent loyalty is not solely determined by financial factors but is also influenced by psychological conditions such as job satisfaction, making the relationship among variables more complex. This study aims to analyze the effect of incentives and Islamic compensation on agent loyalty with job satisfaction as a mediating variable in Sharia insurance in Medan City. The research employs a quantitative approach with a causal associative design, using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The population consists of 400 agents, with a sample of 83 respondents selected using the Slovin formula. Data were collected through Likert-scale questionnaires and analyzed using SmartPLS. The results indicate that incentives and Islamic compensation have a positive and significant effect on job satisfaction, but do not directly influence agent loyalty. Job satisfaction has a positive and significant effect on agent loyalty. Furthermore, job satisfaction does not mediate the effect of incentives on loyalty, but fully mediates the effect of Islamic compensation on agent loyalty. These findings highlight the crucial role of job satisfaction in building sustainable agent loyalty.